Transmission of Atypical Bovine Prions to Mice Transgenic for Human Prion Protein - Vincent Béringue (Emerging Infectious Diseases, 2008)
To assess risk for cattle-to-human transmission of prions that cause uncommon forms of bovine spongiform encephalopathy (BSE), we inoculated mice expressing human PrP Met129 with field isolates. Unlike classical BSE agent, L-type prions appeared to propagate in these mice with no obvious transmission barrier. H-type prions failed to infect the mice.